2017
DOI: 10.1038/s41598-017-10317-x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and trabecular morphology is altered in the limb bones of mice artificially selected for faster skeletal growth

Abstract: Bone strength is influenced by mineral density and macro- and microstructure. Research into factors that contribute to bone morphology and strength has focused on genetic, environmental and morphological factors (e.g., body mass index), but little is known regarding the impact of rates of skeletal elongation on adult skeletal morphology and strength. Using micro-CT, we examined the impact of rates of skeletal elongation on bone cortical and trabecular morphology, and on rates of estrogen-dependent bone loss in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 63 publications
2
21
0
Order By: Relevance
“…Specifically, the tibia's cross-sectional area and polar section modulus in LS1 did not change appreciably, which led us to predict that it is significantly less resistant to bending moments. In a related study (Farooq et al 2017), we found that tibia trabecular microarchitecture had been substantially altered in parallel with increases in tibia length in both Longshanks lines, potentially altering its ability to withstand compressive loads. In the present study, we investigated whether the altered shape of the Longshanks tibia has impacted its strength and elastic properties.…”
Section: Introductionmentioning
confidence: 66%
“…Specifically, the tibia's cross-sectional area and polar section modulus in LS1 did not change appreciably, which led us to predict that it is significantly less resistant to bending moments. In a related study (Farooq et al 2017), we found that tibia trabecular microarchitecture had been substantially altered in parallel with increases in tibia length in both Longshanks lines, potentially altering its ability to withstand compressive loads. In the present study, we investigated whether the altered shape of the Longshanks tibia has impacted its strength and elastic properties.…”
Section: Introductionmentioning
confidence: 66%
“…Some of these variables have been demonstrated to follow non‐linear patterns of change over the lifespan. Mice selectively bred for accelerated skeletal growth had significantly less BV/TV, Tb.N, and Tb.Th than controls (Farooq et al ), indicating that some aspects of trabecular bone quality could be compromised during periods of rapid postnatal growth. Intriguingly, BV/TV and Tb.N decrease between 6 and 12 months of age in the proximal human femur, with the lowest values for these parameters occurring in individuals just under 1 year of age.…”
Section: Discussionmentioning
confidence: 99%
“…Breeders were selected at eight weeks, at which point longitudinal tibia growth is over 97% complete (Farooq et al. , see further). Longshanks mice at generation F14 showed an increase of 9–13% in tibia length relative to body mass.…”
Section: Methodsmentioning
confidence: 99%